THE STUDY OF THE ISSUE OF MEDICINE IN RELIGIOUS TEACHINGS - Alidjanova Lazizaxon Abbasovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The religion of Christianity and Islam is not just a religious doctrine, they are a way of life that covers all aspects of everyday life and sets socio-cultural, moral-household, and medical-spiritual norms. Also, Medicine is free from the influence of religion, so both Christian and Islamic theologians and medical staff have studied theology and methods of treatment parallel.